Advance in Orthopedic Trauma Surgery - Rosslenbroich, Steffen; Oh, Chang-Wug (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The field of orthopedic trauma has always been a discipline cahacterized by rapid innovation and creative evolution. We see evolution in every facet of orthopedic surgery, ranging from the transformation of the understanding of implant design and biomechanics to the understanding and monitoring of fracture healing and the management of complications. This Reprint includes many articles discussing topics, such as distal radius fractures, hip fractures, osteoarthritis, ankle fractures, acetabular fractures, and anterior cruciate ligament reconstruction.